Structural and optical properties of nanocrystalline silicon on teflon substrate by RF magnetron sputtering / Norhidayatul Hikmee Mahzan, Shaiful Bakhtiar Hashim and Sukreen Hana Herman - Mahzan, Norhidayatul Hikmee; Hashim, Shaiful Bakhtiar; Herman, Sukreen Hana (2017)
The potential of nanocrystalline silicon (nc-Si) on opto-electronic properties for thin films transistor (TFT) and solar cells applications have been extensively studied. Recently, the application of flexible substrates rapidly rising to form a new electronics large area circuit such as solar cell, flat panel displays (FPDs) and wearable electronic devices. A nc-Si thin film was successfully deposited on flexible substrates by using radiofrequency (RF) magnetron sputtering at room temperature. The effects of structural and optical properties of Argon gas flow rate have been studied. The Field effect scanning electron microscopy (FESEM) was used to analyze the structural properties of thin films. Based on the FESEM images, there is no significant different for all deposited samples, but from FESEM measurement, it showed the average particles size increase from 12.7 to 15.8 nm when the Ar gas flow rate increases from 40 to 100 sccm. The optical properties were measured by using UV-Vis- NIR spectrophotometer (JASCO V-670 EX UV-VIS-NIR Spectrophotometer) with the wavelength ranges between 300 nm and 800 nm. From the results, it shows that the optical transmittance for both on glass and Teflon substrates shown no difference. The optical transmittance result can be associated with the thickness of thin films which the thicker thin film absorbed more lights then leaded to the transmittance decrease.